Pengembangan Sistem Informasi Penjualan Velg Mobil Berbasis Web dengan Kerangka Kerja Agile Scrum - Roger Skavinsky Teddy; Lisa Amelia Fransen (MDP Student Conference, 2026)
The rapid growth of information technology encourages small and medium enterprises to adopt digital systems to improve operational efficiency. PD VELGSECONDPLG is a business engaged in the sale of new and used car wheels, which previously relied on manual transaction records. This condition caused data inaccuracies, delayed reporting, and difficulties in inventory control. This study aims to develop a web-based sales information system that integrates product management, sales and purchase transactions, inventory control, payment processing, trade-in services, and reporting. The system was developed using the Agile Scrum methodology to ensure flexibility and continuous user feedback. The Laravel framework and MySQL database were used for system implementation. System testing was carried out using black box testing. The results show that all system functionalities operate according to user requirements. The proposed system improves data accuracy, operational efficiency, and service quality at PD VELGSECONDPLG.